Digital citizenship dalam Pendidikan: Pemetaan Tren Penelitian melalui Analisis Bibliometrik - Herisman, Muh; P, Reski; Heri, Ririn Nurfaathirany; Nur, Rahmat; Hasanah, Nur Hafizal; Alex, Alex (Universitas Lambung Mangkurat, 2026)
The fast changes in digital technology have transformed how education is conducted, while simultaneously positioning digital citizenship as an increasingly essential competency. This concept not only pertains to the skills required to use technology but also encompasses attitudes, responsibilities, and ethics within digital spaces. Although studies on digital citizenship have been growing, a comprehensive overview of the research trajectory remains limited. This article aims to map the research trends on digital citizenship in education through a bibliometric analysis based on Scopus data. Data were collected using the keywords “digital citizenship” and “education” for the publication period 2005–2026, resulting in 188 articles that were analyzed using Biblioshiny, following the PRISMA selection framework. The analysis revealed a significant increase in publications, particularly after 2021. The United States emerged as the country with the highest publication output, followed by several European and Asian countries. In terms of research themes, studies largely focus on digital literacy, digital competence, citizenship education, and the use of technology in learning. The COVID-19 pandemic further accelerated interest in this topic, especially in the context of online learning. However, author collaboration networks remain fragmented and do not yet show strong cross-cluster connectivity. In addition, issues such as digital equity and digital activism appear only marginally in the literature. These findings indicate that, despite rapid growth in this field, there remains ample opportunity to strengthen more critical and collaborative approaches in future research.